2018
DOI: 10.1128/aac.00770-18
|View full text |Cite
|
Sign up to set email alerts
|

Increased Doses Lead to Higher Drug Exposures of Levofloxacin for Treatment of Tuberculosis

Abstract: Patients with multidrug-resistant tuberculosis in Peru and South Africa were randomized to a weight-banded nominal dose of 11, 14, 17, or 20 mg/kg/day levofloxacin (minimum, 750 mg) in combination with other second-line agents. A total of 101 patients were included in noncompartmental pharmacokinetic analyses. Respective median areas under the concentration-time curve from 0 to 24 h (AUC) were 109.49, 97.86, 145.33, and 207.04 μg · h/ml. Median maximum plasma concentration () were 11.90, 12.02, 14.86, and 19.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 11 publications
(7 reference statements)
2
21
0
Order By: Relevance
“…Given Lfx's variable degree of protein binding (24 to 40%) in different individuals, we found large interindividual variation in salivary concentrations (20). The results obtained from plasma samples were more homogeneous and consistent with recently published studies on MDR-TB patients by van't Boveneind-Vrubleuskaya et al and Peloquin et al, with similar median observed AUC 0 -24 and C max values (4,15). In theory, several factors could explain the high interindividual variability in saliva, such as salivary pH in combination with drug pKa, salivary flow rate, and mechanism of drug transport (passive or active) (23,24).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Given Lfx's variable degree of protein binding (24 to 40%) in different individuals, we found large interindividual variation in salivary concentrations (20). The results obtained from plasma samples were more homogeneous and consistent with recently published studies on MDR-TB patients by van't Boveneind-Vrubleuskaya et al and Peloquin et al, with similar median observed AUC 0 -24 and C max values (4,15). In theory, several factors could explain the high interindividual variability in saliva, such as salivary pH in combination with drug pKa, salivary flow rate, and mechanism of drug transport (passive or active) (23,24).…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, a plasma AUC 0 -24 above 75 (if the MIC is 0.5 mg/liter) or 146 (if the MIC is 1 mg/liter) will be needed to attain the optimal target exposure for efficacy. With standard 750 to 1,000 mg once daily dose, desired median peak concentration (C max ) was 8 to 13 mg/liter, while the median time to reach C max (t max ) was 1 to 2 h and the median half-life (t 1/2 ) was 6 to 8 h (13)(14)(15). Lfx demonstrated good penetration in extravascular body sites such as cerebrospinal fluid and cavitary lesions, due to rapid absorption and high volume of distribution (16,17).…”
mentioning
confidence: 99%
“…Similarly, “Opti-Q” was a double-blinded, randomized, dose-ranging clinical trial conducted on 101 patients with MDR-TB. The patients received LVX at 11, 14, 17, or 20 mg/kg/day and achieved median AUC 0–24 values of 109, 98, 145, and 207 mg ⋅ h/liter, respectively, suggesting that dose increase produces a relatively linear exposure increase (24). Recently, the STREAM trial has reported a higher number of patients developing QTc prolongation in the short, high-dose MOX regimen compared to the long, conventional one (31 [11%] versus 9 [6%], P = 0.14) (25).…”
Section: Discussionmentioning
confidence: 99%
“…During February to December 2017, a convenience sample of children aged 2 to 10 years who had been on treatment for Ͼ1 month were enrolled in the pharmacokinetic study with written informed consent from parents/guardians. Venous samples (1 ml) were drawn immediately after medication administration and after 1, 2, and 6 h; in previously published studies of TB patients, maximum drug concentration (C max ) typically occurred 1 to 2 h postdose (7,11,12). Levofloxacin serum concentrations were measured at the University of Florida (Gainesville, FL), using a validated high-pressure liquid chromatography assay with tandem mass spectrometry (LC-MS/MS) detection (11).…”
mentioning
confidence: 99%
“…Venous samples (1 ml) were drawn immediately after medication administration and after 1, 2, and 6 h; in previously published studies of TB patients, maximum drug concentration (C max ) typically occurred 1 to 2 h postdose (7,11,12). Levofloxacin serum concentrations were measured at the University of Florida (Gainesville, FL), using a validated high-pressure liquid chromatography assay with tandem mass spectrometry (LC-MS/MS) detection (11). A noncompartmental pharmacokinetic analysis was performed to estimate pharmacokinetic parameters using Phoenix v7.0 (Certara LP, Princeton, NJ).…”
mentioning
confidence: 99%